Faecal Indicator Organisms in Frozen Prawn Products.II. Survival of the Organisms During Freezing and Frozen Storage - Lekshmy, A (Fishery Technology, 1964)
Faecal Indicator Organisms in Frozen Prawn Products.II. Survival of the Organisms During Freezing and Frozen Storage